HUBUNGAN MOTIVASI BELAJAR DENGAN PRESTASI AKADEMIK MAHASISWA OLAHRAGA - Sitti Fatimah Azzahra.M; Wildayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship between learning motivation and academic achievement of sports program students. Learning motivation is a psychological factor that plays a crucial role in determining a person's academic success, especially for students who have a dual burden between academic demands and physical training. The research method used is correlational with a quantitative approach. The research sample consisted of 120 students selected using stratified random sampling technique from four active academic years. Data collection instruments used a learning motivation questionnaire that has been tested for validity and reliability, as well as Grade Point Average (GPA) data obtained from the university's academic system. Data analysis used Pearson correlation and simple linear regression with a significance level of α = 0.05. The results showed a positive and significant relationship between learning motivation and academic achievement of sports students (r = 0.672; p < 0.001). The coefficient of determination shows that learning motivation contributes 45.2% to academic achievement. Intrinsic motivation proved to have a stronger correlation than extrinsic motivation on student GPA. It was concluded that improving learning motivation, especially intrinsic motivation, needs to be a major concern